3'-terminal nucleotide sequence of encephalomyocarditis virus RNA determined by reverse transcriptase and chain-terminating inhibitors. - Zimmern, D (1978)
We have adapted the chain-termination method for determining the nucleotide sequence of DNA of Sanger, Nicklen, and Coulson [(1977) Proc. Natl. Acad. Sci. USA 74, 5463--5467] for use with reverse transcriptase (RNA-directed DNA nucleotidyltransferase) on RNA templates. With this method and using a primer (the octanucleotide pdT7rC) directed at the 3'-terminal poly(A), we have determined a sequence of 166 residues in the genomic RNA of the picornavirus encephalomyocarditis virus.